Pengaruh Minyak Zaitun (Olive Oil) Terhadap Penyembuhan Ruam Popok Pada Bayi Usia 0 - 12 Bulan di Desa Sukobanah Kabupaten Sampang Madura - Setianingsih, Yana Agus; Hasanah, Iradatul (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2017)
Babies often have skin problems because the oil glands are still not fully developed. Skin disorders in babies in Indonesia are the most common of which are diaper rash and prickly heat. Diaper rash is a skin problem in a closed area of ​​diapers that is often experienced by infants or children. Usually areas of the skin that often occur because of diaper rash around the buttocks and genitals. Diaper rash can also be caused by fungi and bacteria. The purpose of this study is to Know the Effect of Olive Oil on the healing of diaper Rash in infants aged 0-12 months. Pre-experimental research design in one group (one group pre test-post test). Samples in this study were 36 babies using purposive sampling sampling technique. Instrument used is observation sheet and analysis used is statistical test of Mc.Nemar. The results after obtaining intervention of olive oil obtained from 36 babies found that as many as 25 babies (69.4%) experienced healing, while 11 babies (21.6%) remained on light diaper rash. Result of analysis with Test of Mc.Nemar in get result with p = 0,000 <a = 0,05 meaning there is Effect of giving olive oil to cure diaper rash in baby 0-12 month. The conclusions of this study, especially mothers who have babies who have diaper rash. It is expected to increase the knowledge and prevention of diaper rash in infants with olive oil especially the problem of diaper rash so that mother can use the correct diaper in her child.